1994
DOI: 10.1007/bf01138462
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization in freshwater animals Ecological implications and molecular approaches

Abstract: The number of cases where the phenomena of hybridization and gene introgression have been found in species interactions is steadily increasing, in both plant and animal taxa. During the last few years, many examples have been detected even in otherwise well-known freshwater animal taxa. We discuss the topic with respect to ecology and evolutionary processes and compare the main potentials and limitations of allozymes, mitochondrial DNA, and RAPD markers to address some important genetic issues of interspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…[Ferris and Whitt, 1979;Chenuil et al, 1999;Tsigenopoulos et al, 2002]; and freshwater tetraploid snails Bulinus truncatus . However, further analyses are necessary to make robust conclusions [Streit et al, 1994].…”
Section: Spontaneous Allopolyploid Originmentioning
confidence: 99%
See 1 more Smart Citation
“…[Ferris and Whitt, 1979;Chenuil et al, 1999;Tsigenopoulos et al, 2002]; and freshwater tetraploid snails Bulinus truncatus . However, further analyses are necessary to make robust conclusions [Streit et al, 1994].…”
Section: Spontaneous Allopolyploid Originmentioning
confidence: 99%
“…Transition from Non-Hybrid Diploidy to Allotetraploidy Streit et al [1994] discussed the possibility of a union of unreduced gametes from 2 diploid species (AA and BB) that could directly produce an allotetraploid AABB without an intermediate triploid bridge ( fig. 2 D).…”
Section: Spontaneous Allopolyploid Originmentioning
confidence: 99%
“…Differences in mitochondrial DNA sequences between hybrids and the maternal species are so small that relatively recent hybridization events should be assumed (Schwenk, 1993). Moreover, Schierwater et al (1994), using RAPD markers, showed that D. galeata x hyalina hybrid individuals possess a greater proportion of nuclear markers from D. hyalina than from D. galeata. Also, recent work on the North American Daphnia galeata rnendotae-Daphnia rosea hybrid complex (Taylor & Hebert, 1993) has revealed that in this hybrid complex backcrossing and introgression occur.…”
mentioning
confidence: 99%
“…When used in phylogenetic analyses, the combination of these two genes with different evolutionary rates serves to identify fish at the species level ( 5 ). Moreover, the given independent variation rate for each gene has allowed the identification of basal phylogenetic relationships and identify any rare case of paraphyly or hybridization between close species ( 6 ).…”
Section: Dna Sequencesmentioning
confidence: 99%